An uncommon case of late-onset congenital diaphragmatic hernia with bloody stool - Keisuke Jimbo; Reiko Kyoudo; Yuta Yazaki; Kana Ohno; Takashi Doi; Atsuyuki Yamataka; Toshiaki Shimizu (Elsevier, 2016)
Late-onset congenital diaphragmatic hernia (CDH) is an uncommon subset of CDH and distinct from neonatal CDH with respect to presenting symptoms, diagnosis, management, and prognosis. In particular, CDH diagnosed after 30 days of age (late-onset CDH) is uncommon and has an atypical presentation and a more favorable prognosis. In the present report, an infantile late-onset CDH case that presented with bloody stool and had a severe clinical course is described. In previous reports, no late-onset CDH case developed bloody stool. After diagnosis with image inspections, emergency surgery was performed. At operation, via the hernia orifice, the jejunum was seen to have prolapsed into the thoracic cavity with focally significant intestinal and mesenteric congestion, but no intestinal necrosis. In general, other disorders such as intussusception may be considered in the differential diagnosis of acute abdomen with bloody stool in patients of this age. However, in such late-onset CDH cases, immediate differentiation from other causes of acute abdomen that present with bloody stool is life-saving.